Radial models and popularization process in the radio of Lima - Alfaro-Moreno, Rosa María (2018)
The process of this investigation clearly demonstrates the precariousness of the knowledge that exists on the radio. Being the most massive means in terms of its ability to arrive, and the most experienced by its volume of production, as well as its varied historical uses, however, is the least explored and investigated. The objectives of communicative research still prioritize the study of those media where the hegemonic economic and ideological sectors in our societies reproduce their power with greater evidence.